Strange Fruit and Patriotic Flowers: E. McKnight Kauffer's Illustrated South. - Knighton, Mary A. (Southern Cultures)
This article discusses literary works by Langston Hughes and William Faulkner in relation to their dust jackets and illustrations by the modernist expatriate American poster artist E. McKnight Kauffer (1890–1954). It argues that Kauffer's life and art are best understood in the context of displacement and exile in response to two world wars, which forced his return to an America in which he no longer felt "at home" by 1940. His prolific output left its mark—on high modernism, on the evolution of book and poster design, even on ads to buy war bonds for textile mills in the South. A globally engaged modernist who for many years abroad looked from the outside in at the U.S. Kauffer made unique contributions to cultural and political representations of African Americans and the South. Most dramatically, in cover art for Faulkner's Intruder in the Dust (1948)—a dust jacket only now being recognized for its subversive implications—Kauffer encodes his own paratextual interpretation of the novel's lynching theme.